Strategic Public Relations Management in Building the Brand ‎Image of Islamic Schools in a Muslim-Minority Context: A ‎Multiple Case Study - Laerosa, Ihsan; Syukur, Fatah; Khoiri, Nur (JPI: Jurnal Pustaka Indonesia, 2025)
This study investigates how strategic public relations (PR) management contributes to the construction of brand image and institutional legitimacy in Islamic schools operating within a Muslim-minority context in Southern Thailand. Using an interpretivist qualitative multiple-case design, the study examined Ma’had Al-Bi’that Ad-Diniah in Yala and Madrasah Darussalam in Narathiwat. Data were generated from seven purposively selected informants two principals, three teachers, and two students through in-depth interviews, participatory observation, and document analysis, and were analyzed through iterative coding, within-case thematic analysis, and cross-case comparison. The findings show that positive brand image was constructed less through promotional intensity than through community engagement, network-based collaboration, value-driven communication, leadership visibility, stakeholder trust, and educational differentiation. In the minority setting, socio-political sensitivity, educational competition, and multicultural communication shaped how Islamic identity was communicated and evaluated. Across the cases, stakeholders interpreted school image through the perceived consistency between institutional messages and everyday educational, ethical, and social practices. The study therefore conceptualizes brand image as a relational and legitimacy-based outcome produced through accumulated stakeholder experience rather than communication exposure alone. Practically, Islamic schools in plural environments should prioritize sustained stakeholder relationships, transparent communication, credible educational quality, and alignment between religious identity and observable organizational practice; these findings also provide a context-sensitive basis for strengthening strategic PR in faith-based education.